Contextual Experiential Learning in Higher Education - Competency in Forecast Patterns and New Demand Realization - SDG 4.7 - Yeung, Shirley Mo Ching (Journal of Posthumanism, 2025)
As supply chains focus on creating value and reducing waste, the author intends to link the concepts of Supply-Chain Operations Reference model (SCOR) with SDG for contextual experiential learning design and management of demands from learners so as to increase value to stakeholders and reduce resources for sustainability. The Supply-Chain Operations Reference (SCOR) model is a widely accepted framework for managing and optimizing supply chain operations. It provides a structured approach to analyzing and improving supply chain performance across five key processes: Plan, Source, Make, Deliver, and Return. In this article, we will apply the SCOR model to the higher education industry with results of 21articles published from 2010 to 2021, that is, application of 1) Contextual Experiential Learning, 2) New Demand Realization, 3) Competency in Forecast Patterns into SCOR model for developing talents with higher demand skills in sustainability, AI application and wellness of self management skills to fulfill the gaps that arised from the pandemic.